Civil control mechanism in the Free Trade Agreements - Nadrdaia, Ada (Politics / პოლიტიკა, 2020)
It has been more than a decade since the European Union (EU) set standards for the international labor rights in its Free Trade Agreements (FTAs). The mentioned standards allow involvement of civil society groups via institutional channel. In particular it entails, implementation of sustainable development and trade part of the FTA through introduction and implementation of labor rights and environmental/climate protection involving Jointly established Domestic Advisory Groups (DAG). Civil society representatives, represented at DAGs are assisting the EU and its Partners / Contracting Parties in fulfilling Trade and Sustainable Development mandate. The DAGs also include stakeholders who ensure sustainable development in terms of environmental / climate / labor protection. The Joint Statements issued by the DAGs of Georgia and the EU during 2016-2019, define the level of involvement of Non-governmental organizations as well as priority issues. At the same time, this is also possible to define their role at different stages of adopting the relevant legislation as well as implementation of the policy. The article reviewed impact of Georgian civil society, namely DAGs in the implementation and management of trade and sustainable development chapter by the Georgian state as stipulated in the Association Agreement. In various countries, studies regarding civil control mechanisms in FTAs are usual practice, although in terms of Georgian context this is a novelty. On balance, since 2014 Georgia has institutionalized public control that focuses on civic control in the implementation of trade and sustainable development issues. Content analysis conducted within the study found that the role of the civil society sector is consistently emphasized and the appropriateness of their involvement is requested and considered by the parties and relevant procedural issues are present.
Keywords: Civil control; Free Trade Agreements